2018
DOI: 10.15739/ijeprr.18.013
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Looking at the increasing trend of suicide in learners globally, the present study is an attempt to investigate the relationship between emotional intelligence and suicidal behaviour among secondary school students in Kitutu Central Sub-County of Kisii County in Kenya. The study employed a concurrent triangulation research methodology where both descriptive cross sectional survey and naturalistic phenomenology designs were used. Probability and non-probability sampling methods were used to sample 120 studentsf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Regarding EI's components, the self-reported healthy well-being and good ability in EI predicted less suicidal thoughts among adolescents in the US, Spain, Kenya (Cha & Nock, 2009;Mamani-Benito, Brousett-Minaya, Ccori-Zuniga, & Villasante-Idme, 2018;Okello & Aomo, 2018) and among adults in Hong Kong (Kwok, 2014). Our finding fits the local culture of Central Vietnam, in which the individual tends to manage and solve problems by themselves.…”
Section: Determinants Of Lifetime Suicidal Thoughtssupporting
confidence: 68%
See 1 more Smart Citation
“…Regarding EI's components, the self-reported healthy well-being and good ability in EI predicted less suicidal thoughts among adolescents in the US, Spain, Kenya (Cha & Nock, 2009;Mamani-Benito, Brousett-Minaya, Ccori-Zuniga, & Villasante-Idme, 2018;Okello & Aomo, 2018) and among adults in Hong Kong (Kwok, 2014). Our finding fits the local culture of Central Vietnam, in which the individual tends to manage and solve problems by themselves.…”
Section: Determinants Of Lifetime Suicidal Thoughtssupporting
confidence: 68%
“…In a laboratory-based study, Cha and Nock (2009) found among 54 US female adolescents (age ranged from 12 to 19 years) that EI was a protective factor against suicidal ideation and attempts. This result was duplicated among secondary school students in a recent cross-sectional study in Kenya (Okello & Aomo, 2018) and depressed adolescents in Iran (Abdollahi, Khanbani, Ghahfarokhi, & Carlbring, 2016). However, the correlation between EI and suicidal ideation among adolescents in many cultures is unknown, including in Southeast Asia.…”
Section: Introductionmentioning
confidence: 93%
“…Students will lack writing motivation if they do not successed in writing skills. Which can lead to self-confidence issues (Goleman, 1995;Okello & Aomo, 2018;Sarkar and Banerjee, (2019). The evaluation of writing proficiency among secondary school students has included an examination of cognitive intelligence (Côté, 2017;Esmaeili et al, 2018;Pishghadam, 2009;Rad et al, 2014).…”
Section: Emotional and Motivational Intelligence In Writing Performancementioning
confidence: 99%
“…In contrast, Alavinia et al (2012) conducted a correlational survey involving 1160 senior secondary school students in the Federal Capital territory of Abuja, Nigeria and revealed that the average level of EI was attributed to the students' experience in secondary school. According to Okello and Aomo's (2018) study on the relationship between EI and suicidal behavior among secondary school students, the majority of the students (55.7%) were proficient in identifying their emotions. The study sampled 120 students from 20 schools in Kisii County.…”
Section: Emotional and Motivational Intelligence In Writingmentioning
confidence: 99%
See 1 more Smart Citation